Genetic diversity and population structure of three Schizothorax curvilabiatus populations in the Yarlung Zangbo River based on mitochondrial genes - Su, Qi; He, Kai; Yang, Peican; Zhang, Chi (Frontiers in Ecology and Evolution, 2026)
BackgroundSchizothorax curvilabiatus is a commercially important freshwater fish endemic to the lower reaches of the Yarlung Zangbo River. However, its fishery resources have been severely depleted due to human activities, leading to a scarcity of data regarding its genetic characteristics. This study aims to assess the genetic diversity and population structure of this species to provide a scientific basis for its conservation.MethodsThree mitochondrial DNA markers—Cytochrome b (Cyt b), Control Region (D-loop), and Cytochrome Oxidase Subunit I (COI)—were sequenced and analyzed. A total of 100 samples were collected from three natural populations in the lower Yarlung Zangbo River: Motuo (MT), Palong (PL), and Chayu (CY).ResultsHigh overall haplotype diversity (Hd: 0.889–0.951) but relatively low nucleotide diversity (Pi: 0.00450–0.0111) were observed. Notably, the PL population exhibited the lowest genetic diversity across all markers. Significant genetic differentiation was detected between the PL population and the other two populations (MT and CY), supported by FST indices, gene flow (Nm) estimates, and Analysis of Molecular Variance (AMOVA), which revealed that most variation resided within populations (>83%). Both Neighbor-Joining (NJ) phylogenetic trees and haplotype network analyses indicated a distinct geographical lineage pattern, with the PL and CY populations showing a distant genetic relationship.DiscussionAlthough S. curvilabiatus maintains substantial overall genetic diversity, the low diversity within specific populations (particularly PL) and the significant inter-population differentiation highlight the vulnerability of its germplasm resources. These findings provide crucial insights into the genetic background of the species and offer valuable guidance for the conservation and sustainable management of its genetic resources.